Črna jelša (Alnus glutinosa (L.) Gaertn.) - drevo z zlim slovesom - Torelli, Niko (Les (Ljubljana), 2002)
A detailed description is presented of the etymology, tree lore, folk beliefs and famous erraneous translation of the Danish elle(k)konge into German Erkönig by J. W. Goethe has a poem on him, set to music by F. Schubert and C. Loewe.
Keywords: črna jelša; Alnus glutinosa; etimologija; etymology